HAK KONSTITUSIONAL ATAS AIR PASCA DIHAPUSNYA UNDANG UNDANG NOMOR 7 TAHUN 2004 TENTANG SUMBER DAYA AIR OLEH MAHKAMAH KONSTITUSI - Nova Yarsina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The purpose of this study is to examine human rights over water after the abolition of Law Number 7 of 2004 concerning Water Resources by the Constitutional Court. The research method used is normative juridical. Later there was an opinion that if the state was unable to guarantee the fulfillment of human rights over water, then the water supply was carried out by a third party. The state must regulate the appropriateness of control over water sources, affordability of prices, guarantees for water health. For the realization of these things, a system of regulation must be made. An independent regulatory body can also be formed, public participation, and sanctions against violations. In essence, every regulation issued by the local government related to water use actually makes water as